A study on the density wave oscillation relative stability turning point of uniform and cosine heat flux profiles in parallel channels. (May 2019) - Ma, Zaiyong; Zhang, Luteng; Sun, Wan; Bu, Shanshan; Pan, Liangming
Highlights: Features of RSTP of the profiles were studied. At zero outlet coefficient, Nsub/Npch at RSTP could be almost constant. The oscillation frequency ratio of the profiles at RSTP may be constant. Abstract: Existing studies have shown that heat flux profile is a key parameter influencing the system stability boundary, and in practical systems, heat flux profile along the flow channel can be very complex and would change with operation conditions. For the stability analysis of a certain system, instead of obtaining all the stability boundaries under various heat flux profiles, it may be more wise to find the stability boundary of the most conservative heat flux profiles, and in this case it is important to have a knowledge of the relative stability turning point (RSTP) of given profiles. In this paper we performed a study on the properties of parallel channel density wave oscillation (DWO) RSTP of two given heat flux profiles, mainly based on the most studied uniform and cosine profiles. A lot of different operation conditions were calculated to find the effects of operation parameters including inlet resistance coefficient, outlet resistance coefficient, mass flow and pressure on RSTP and to obtain the properties of RSTP characteristics of the profiles. Results showed that RSTP in the Nsub-Npch plane can change with inlet resistance coefficient, outlet resistance coefficient and mass flow, but the pressure effect may be ignorable. For zero outlet resistance coefficient, RSTP of the profiles studied in our paper would almost follow a constant ratio of the subcooling number (Nsub) and phase change number (Npch), and this can be used to determine the relative stability of the profiles conveniently. Also, it was found that outlet resistance coefficient increase would reduce the value of Nsub/Npch and the single phase length ratio difference of the profiles at RSTP.